Markedness Neutralisation and the Unity of Opposites in Heraclitus (Revista Archai, 2024)
In this article, I shed new light on a misunderstood aspect of Heraclitus’ style. The opposites employed by Heraclitus are often of equal status except that one member of each pair may also appear as a designation for the encompassing whole. I begin by discussing two interpretations of this phenomenon, which were put forward by Roman Dilcher and Alexander Mourelatos. The phenomenon is, I suggest, better understood as being an example of what is known as markedness neutralisation. I argue that this phenomenon should be interpreted as further undermining what Mourelatos identified as a naïve paratactic metaphysics of mere things (NMT), to which Heraclitus was reacting by beginning to develop a hypotactic metaphysics of hierarchies and dependencies as part of a view of the world as being logos-textured. Further, I consider a series of three problems that were put forward by Dilcher, which he thinks must be addressed by anyone who claims that Heraclitus held a unity of opposites thesis. I also consider some related issues, and provide some responses.